Group Exhibition-Rolling Snowball/2’, Wonderland Lotte Square, Quanzhou - Antoniou, Klitsa (My University, 2026)
Rolling Snowball/2’, Wonderland Lotte Square, Quanzhou, China. Curated by Ineke Gudmundsson